Association of Low Serum Ferritin Level with Non-Scarring Alopecia in Women from Punjab, Pakistan: Low Ferritin and Non-Scarring Alopecia - Latif, Kinza; Saqib, Zareen; Bashir, Bushra; Riaz, Saira (Pakistan Journal of Health Sciences, 2025)
Hair loss in women is often linked to nutritional deficiencies, especially low serum ferritin. Reduced ferritin may impair hair growth and contribute to non-scarring alopecia, though existing studies show mixed results. Objectives: To determine the association between low serum ferritin levels and non-scarring alopecia in women from Punjab, Pakistan. Methods: This Case-control study was conducted at the Department of Dermatology, Allam Iqbal Memorial Teaching Hospital, Sialkot, from May 2025 to August 2025. A total of 102 women aged 18–55 years were enrolled, including 51 diagnosed with non-scarring alopecia and 51 age-matched controls with unrelated dermatological conditions. Venous blood samples were analyzed for hemoglobin, ESR, and serum ferritin using ELISA. Serum ferritin <15 ng/mL was categorized as low. Data were analyzed using SPSS v26 and DataTabs. Independent sample t-test compared mean values, chi-square tested categorical associations, and logistic regression determined the predictive value of serum ferritin. Results: The mean age of participants was 36.0 ± 10.8 years. Among cases, alopecia areata was most frequent (45.1%), followed by androgenetic alopecia (27.5%) and telogen effluvium (27.5%). Mean ferritin and hemoglobin levels were lower in cases, while ESR was slightly higher. Low ferritin was present in 41.2% of cases versus 19.6% of controls (χ² = 5.61, p=0.018). Logistic regression showed low ferritin significantly predicted alopecia (OR=2.87, 95% CI: 1.18–6.98, p=0.02). Conclusions: Low serum ferritin is significantly associated with non-scarring alopecia in women. Routine assessment of ferritin may help in identifying iron deficiency as a modifiable factor in patients presenting with hair loss.